2002
DOI: 10.1097/00005537-200210000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Diplopia Following Endoscopic Orbital Decompression: The Orbital Sling Technique

Abstract: The incidence of new-onset or worsened diplopia following endoscopic decompression was significantly lower for the orbital sling group compared with control subjects (0% vs. 29.2%, respectively [ =.038]). No patients in the orbital sling group developed new-onset diplopia following surgery. Of the eight patients with pre-existing diplopia from the orbitopathy, double vision improved in four patients (50%) and was unchanged in the remaining four patients (50%). The mean reduction in proptosis was comparable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 11 publications
0
62
2
3
Order By: Relevance
“…In three studies on transnasal decompression, the reported incidence of NOD ranged from 22 20 to 29% 18 before recalculation, and from 44 18 to 58% 16 after recalculation. After recalculation, a comparable high frequency of NOD was found in one study that predominantly contained patients with CON 16 and in two studies that predominantly contained patients with DGO.…”
Section: Other Side Effects and Complicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In three studies on transnasal decompression, the reported incidence of NOD ranged from 22 20 to 29% 18 before recalculation, and from 44 18 to 58% 16 after recalculation. After recalculation, a comparable high frequency of NOD was found in one study that predominantly contained patients with CON 16 and in two studies that predominantly contained patients with DGO.…”
Section: Other Side Effects and Complicationsmentioning
confidence: 99%
“…After recalculation, a comparable high frequency of NOD was found in one study that predominantly contained patients with CON 16 and in two studies that predominantly contained patients with DGO. 18,20 In two studies on decompression by orbital fat removal, the reported (and recalculated) frequency of NOD ranged from 0 to 3%. 41,42 NOD and indication for surgery In only three studies, 4,24,37 in which both patients with DGO and those with CON were included, the authors had calculated the incidence of NOD according to the indication for surgery.…”
Section: Other Side Effects and Complicationsmentioning
confidence: 99%
See 3 more Smart Citations